BEBERAPA PANDANGAN HISTORIS DAN PRAKTIK PELAKSANAAN DOKTRIN REBUS SIC STANTIBUS DALAM HUKUM INTERNASIONAL - Basarah, Mochamad (Jurnal Wawasan Yuridika, 2011)
By rebus sic stantibus, the countries with their efforts could demand their rights back. Differences in terminology can thus blurthe differencesand the similarities in theimplementation. The International Law Commission has rejected the usage of the terminology of rebus sic stantibus. They prefer using the terminology of the doctrine of fundamental changes on equality and justice reasons, and getting rid of the terminology of rebus sic stantibus as it is assumed to cause unintended effects. This doctrine, in fact has been performed, primarily after the end of the war between the allies and Germany. A conditional change can be expressed, although it can not properly be predicted before. It depends on the intention and the hopes of the concerned parties, and intended change characteristic as well which may appear from suspension and restriction of doctrine implementation according to the circumstances of that time.Keywords: Rebus sic stantibus - International Law -Implementation